(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
Recent anatomic observations of the types of Lithophyllum contii Mastrorilli, 1967, Lithophyllum embergeri Mastrorilli, 1968, Mesophyllum flexile Mastrorilli, 1968 and Mesophyllum rigidum Mastrorilli, 1968 urged their revision under modern taxonomic schemes. Lithophyllum contii Mastrorilli, 1967 is transferred to the subfamily Mastophoroideae and the new combination Neogoniolithon contii is proposed. L. giammarinoi, L. embergeri, M. flexile and M. rigidum are considered to be younger heterotypic synonyms of L. contii, originally established on the basis of anatomical details herein considered to be artefacts due to improper orientation of studied thalli. Each species is critically analysed on the basis of original Mastrorilli’s collections (Genoa University, Dip.Te.Ris) and additional material collected at the type localities.